The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/dme.12742
|View full text |Cite
|
Sign up to set email alerts
|

A genetic diagnosis of maturity‐onset diabetes of the young (MODY): experiences of patients and family members

Abstract: Patients and family members are generally positive about genetic testing for MODY. More education of healthcare professionals and attention on the part of diabetes organizations is needed to increase awareness and optimize care and support for people with MODY.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
1
11
0
1
Order By: Relevance
“…Parents receiving no diagnosis vacillated between accepting that they have to continue living with uncertainty and longing for a continuation of research in order to receive a diagnosis at a later stage. Whereas most of these experiences cohere with previous studies in the context of rare genetic syndromes (Bosma et al 2015; Brooks-Howell 2006; Graungaard and Skov 2006; Hallberg et al 2010; Reiff et al 2012; Skirton 2001; Webb 2005), they have not been studied in a largely unselected patient cohort with a presumed genetic disease. For example, the likelihood of these patients receiving a genetic diagnosis using WES was much greater than when testing for genetic syndromes by gene-specific Sanger sequencing tests.…”
Section: Discussionsupporting
confidence: 72%
“…Parents receiving no diagnosis vacillated between accepting that they have to continue living with uncertainty and longing for a continuation of research in order to receive a diagnosis at a later stage. Whereas most of these experiences cohere with previous studies in the context of rare genetic syndromes (Bosma et al 2015; Brooks-Howell 2006; Graungaard and Skov 2006; Hallberg et al 2010; Reiff et al 2012; Skirton 2001; Webb 2005), they have not been studied in a largely unselected patient cohort with a presumed genetic disease. For example, the likelihood of these patients receiving a genetic diagnosis using WES was much greater than when testing for genetic syndromes by gene-specific Sanger sequencing tests.…”
Section: Discussionsupporting
confidence: 72%
“…This impacts negatively on the quality of clinical care, with patients likely to receive suboptimal or inappropriate treatment, including insulin with no resulting improvement in outcomes. Bosma et al noted that MODY patients and their families were disappointed by the lack of knowledge, guidance and advice about MODY from health professionals [19]. The patients themselves also were often not surprised with being diagnosed with an atypical form of diabetes ie non-type 1 and non-type 2 as they discerned differences as compared with those affected by Type 1 and Type 2 diabetes.…”
Section: Algorithmsmentioning
confidence: 99%
“…Multiple studies have demonstrated the improved patient experience resulting from a genetic diagnosis of MODY. (16, 19, 20) A recent study modeling the cost-effectiveness of MODY genetic testing in all type 2 diabetes patients determined that the practice would surpass the cost-effectiveness thresholds that are used for resource-allocation decisions. (21) In addition to the benefits of MODY genetic testing, genetic diagnoses for KCNJ11 or ABCC8 mutations in most NDM patients allows them to transition from insulin injections to high-dose sulfonylureas, which have dramatic effects on glycemic control.…”
Section: Importance Of Genetic Mody Diagnosismentioning
confidence: 99%